Adsorption induced enzyme denaturation: the role of polymer hydrophobicity in adsorption and denaturation of alpha-chymotrypsin on allyl glycidyl ether (AGE)-ethylene glycol dimethacrylate (EGDM) copolymers - Lahari, Challa; Jasti, Lakshmi Swarnalatha; Fadnavis, Nitin W.; Sontakke, Kalpana; Ingavle, Ganesh C.; Deokar, Sarika Babasaheb; Ponrathnam, Surendra (Langmuir, 2010)
Effects of changes in hydrophobicity of polymeric support oil structure and activity of alpha-chymotrypsin (E.C.3.4.21.1) have been studied with copolymers of allyl glycidyl ether (AGE) and ethylene glycol dimethacrylate (EGDM) with increasing molar ratio of EGDM to AGE (cross-link density 0.05 to 1.5). The enzyme is readily adsorbed front aqueous buffer at room temperature following Langmuir adsorption isotherms in unexpectedly large amounts (25% w/w). Relative hydrophobicity of the copolymers has been assessed by studying adsorption of naphthalene and Fmoc-methionine by the series of copolymers from aqueous solutions. Polymer hydrophobicity appears to increase linearly oil increasing cross-link density from 0.05 to 0.25. Further increase in cross-link density Causes a decrease in naphthalene binding but has little effect on binding of Fmoc-Met. Binding of alpha-chymotrypsin to these copolymers follow the trend for Fmoc-methionine binding, rather than naphthalene binding, indicating involvement of polar interactions along with hydrophobic interactions during binding of protein to the polymer. The adsorbed enzyme undergoes extensive denaturation (ca. 80%) with loss of both tertiary and secondary structure on contact with the copolymers as revealed by fluorescence, CID and Raman spectra of the adsorbed protein. Comparison of enzyme adsorption behavior with Eupergit C, macroporous Amberlite XAD-2, and XAD-7 Suggests that polar interactions of the EGDM ester functional groups with the protein play a significant role in enzyme denaturation.

Adsorption induced enzyme denaturation: the role of protein surface in adsorption induced protein denaturation on allyl glycidyl ether (AGE)-ethylene glycol dimethacrylate (EGDM) copolymers - Thudi, Lahari; Jasti, Lakshmi Swarnalatha; Swarnalatha, Y.; Fadnavis, Nitin W.; Mulani, Khudbudin Baban; Deokar, Sarika Babasaheb; Ponrathnam, Surendra (Colloids and Surfaces B-Biointerfaces, 2012)
The effects of protein size on adsorption and adsorption-induced denaturation of proteins on copolymers of allyl glycidyl ether (AGE)-ethylene glycol dimethacrylate (EGDM) have been studied. Different responses were observed for the amount of protein adsorbed and denatured on the polymer surface for different proteins (trypsin, alchol dehydrogenase from baker's yeast (YADH), glucose dehydrogenase (GDH) from Gluconobacter cerinus, and alkaline phosphates from calf intestinal mucosa (CIAP). Protein adsorption on the copolymer with 25% crosslink density (AGE-25) was dependent not only on the size of the protein but also on the presence of glycoside residues on the protein surface. Adsorption and denaturation of proteins follows the order YADH > trypsin > GDH >> CIAP although the molecular weights of the proteins follow the order YADH > CIAP > GDH > trypsin. The lack of correlation between amount of adsorbed protein and its molecular weight was due to the presence of glycoside residues on CIAP and GDH which protect the enzyme surface from denaturation. Enzyme stabilities in aqueous solutions of 1-cyclohexyl-2-pyrrolidinone (CHP) correlate well with the trend in denaturation by the copolymer, strongly suggesting that hydrophobic interactions play a major role in protein binding and the mechanism of protein denaturation is similar to that for water-miscible organic solvents. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: 1-Cyclohexyl-2-pyrrolidinone; Adsorption; Alcohol dehydrogenase; Alkaline phosphatase; allyl glycidyl ether; Denaturation; ethylene glycol dimethacrylate; Glucose dehydrogenase; Trypsin